Analisis Perilaku Pasien Hemodialisis dalam Pengontrolan Cairan Tubuh - Wahyu Wijayanti; Laily Isro'in; Lina Ema Purwanti (Indonesian Journal for Health Sciences, 2017)
The behavior of the fluid control in hemodialysis patients can determine the success of hemodialysis therapy. Hemodialysis patients who do not abide by controlling the fluid can develop complications such as congestive heart failure. This study aimed to identify the behavior of hemodialysis patients in the control of body fluids in the Hemodialysis Dr. Harjono Ponorogo General Hospitals. The design used is descriptive with a population of 250 hemodialysis patients in Dr. Harjono Ponorogo General Hospitals. Total sample of 38 respondents to the sampling technique used was purposive sampling. Data Collection using questionnaires. Data were analyzed using T-Score categories of good and bad behavior. From The study, of 38 respondents we obtained 20 respondents (52.63%) had a bad behavior and 18 respondents (47.36%) had good behavior. The behavior of the fluid control in hemodialysis patients can be improved by providing better support from health professionals and families of patients during hemodialysis and self-efficacy training. Recommendations for further research conduct research on "The Relationship Behavior In Hemodialysis Patients With Body Fluids Controls Risk of Complications.